Effect of porous slab thickness and Darcy number on thermohydraulic transport characteristics of Ag–TiO2/water hybrid nanofluid flow‐through partially porous wavy channels. Issue 1 (8th September 2022) - Kumar, Prince; Pandey, K. M.
Abstract: The present article investigates the effect of varying porous slab thicknesses ( S = 0–0.4) and Darcy number ( Da = 10 −6 –10 −2 ) on the thermohydraulic performance of three different corrugated channels (triangular, sinusoidal, and trapezoidal) embedded with partially filled porous media. Ag–TiO2 /water hybrid nanofluid ( ϕ φ = 0–0.04) is taken as coolant flowing at Re = 400. Results revealed that the thermal performance (average Nusselt number, Nu avg and enhancement ratio, ER ) augments with the increase in porous slab thickness and decrease in Darcy number. However, the hydraulic performance reduces (i.e., an increase in pressure drop). To check the viability of the cooling system performance factor ( PF ) is evaluated which demonstrates variation in thermal performance considering pressure drop penalty also. It is demonstrated that among all configurations, the trapezoidal channel with porous slab thickness ( S = 0.4) and Darcy number ( Da = 10 − 4 ) gives maximum enhancement thermal performance (110%) considering water as a coolant ( ϕ φ = 0). Furthermore, enhancement in thermal performance by 210% is noticed as volume concentration ϕ φ of hybrid nanofluid varies from 0% to 4%. It is also evident that the value of PF for all corrugated channels is lower than 1 indicating the nonviable system. However, for the case of the partially porous plane channel the maximum PF = 1.07.